2017
DOI: 10.1051/bmdcn/2017070203
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of matrix metalloproteinases-1 genotypes to gastric cancer susceptibility in Taiwan

Abstract: Expression of matrix metalloproteinase-1 (MMP1), an interstitial collagenase regulating the extracellular matrix, plays a major role in carcinogenesis of gastric cancer, a leading cause of death worldwide. In literature, the single-nucleotide polymorphism (SNP) promoter -1607 1G/2G (rs1799750) at the MMP1 gene promoter has been reported to alter its own transcription level. While the importance’s of the genotype of MMP1 promoter -1607 has not yet been studied in gastric cancer in Taiwan, our aim was to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 36 publications
0
43
0
2
Order By: Relevance
“…It is well accepted, however, that cartilage degradation is a critical step during OA development. Dysregulated MMP activity is obvious in several pathological conditions associated with loss of normal collagen architecture (Yang et al, 2017). Researchers have therefore proposed that therapeutic strategies should target MMPs in the treatment of arthritis (Troeberg & Nagase, 2012;Wang, Xu, Hunter, & Ding, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is well accepted, however, that cartilage degradation is a critical step during OA development. Dysregulated MMP activity is obvious in several pathological conditions associated with loss of normal collagen architecture (Yang et al, 2017). Researchers have therefore proposed that therapeutic strategies should target MMPs in the treatment of arthritis (Troeberg & Nagase, 2012;Wang, Xu, Hunter, & Ding, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…35,36 In this study, we found that a FAK inhibitor, MEK inhibitors Cytokines, chemokines, and growth factors are known to regulate gene expression through the AP-1 site. 37,38 It has been reported that saponins reduce MMP-1 expression in immortalized human keratinocytes (HaCaT) via AP-1-dependent signaling 39 and that luteolin suppresses IL-1β-induced MMP production by inhibiting AP-1 activation. 40 In this study, AP-1 inhibitors and siRNA reduced IL-1β-induced MMP-1 expression, suggesting that AP-1 activation mediates IL-1β-increased MMP-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Rech et al [ 20 ] uncovered that MMP-1 gene variants were associated with systemic sclerosis. A host of studies also demonstrated that MMP-1 gene rs1799750 polymorphism was related to cancer susceptibility, such as leukemia [ 21 ] and gastric cancer [ 22 ]. We assumed that rs1799750 polymorphism mediated the MMP-1 expression, thereby contributing to the risk for many diseases, which needs further studies to verify it.…”
Section: Discussionmentioning
confidence: 99%